Multi-Configuration Stiffened Panels under Compressive Load: Part 2 â€“ Finite Element Analysis - Ramly, Ramzyzan; Radzi Abdul Ghani, Amir; Effendy Mohd Nasir, Rizal; Mohamed, Zulkifli; Kuntjoro, Wahyu (International Journal of Engineering and Technology, 2018)
Stiffened panels are the structure used in the aircraft wing skin panels. Stiffened panels are often critical in compression load due to its thin structural configuration. This paper is the continuation of the previous work which was focusing on the theoretical aspect. This paper will explore the Finite Element Analysis of the multi-configuration structure of the stiffened panels. Using ANSYS Workbench, the process of drawing the geometry, meshing the model, setting up the boundary conditions, running the program, and obtaining the results were performed. The loads to apply were obtained from the previous research. The results of the FEA shows the critical locations in the stiffened panels such as distortions, deformation, and the stress distributions.Â Â